DISEÑO DE UN BIODIGESTOR ANAERÓBICO PARA LA PRODUCCIÓN DE ABONO EN LA HACIENDA LA FRUTITA, A PARTIR DEL RESIDUO DEL MANGO - Icaza Arreaga, Dariana Cristhell (2023)
This technological project is focused on the development of a Design of an anaerobic biodigester to produce fertilizer in the Hacienda la Frutita, from the residue of the mango with the objective of taking advantage of the waste, minimizing the expenses in the farm and the environmental impact. allowing to regenerate the soil with organic fertilizer to obtain greater production with fewer chemical fertilizers.